Socio Ecological Model (SEM) and Diffusion of Innovation (DOI) Integrated Framework: A Proposal for Integration to Improve Intervention in the Digital Age of Medicine - Yolene Gousse; Joseph Ravenell; Robert Steptoe; Dawn Douglas; Joanne Camille; Chimene Castor (INNOVATIONS in Pharmacy)
Health promotion intervention theory must adapt as evidence grows to support the complexities of social and behavioral health fields. Following the COVID-19 pandemic, digital health continues to grow, requiring a re-evaluation of traditional models’ applicability to these approaches.  The authors propose adapting and integrating the Socio-Ecological Model (SEM) and Diffusion of Innovation (DOI) models for application with digital health to deliver interventions. We also describe the application of the SEM-DOI integration in conjunction with a demonstration project, a digital intervention to improve Metabolic Syndromes (MetS) health outcomes. Future health interventions may consider the proposed SEM-DOI model to account for individual and community-level factors during implementation and use as a guide for meaningful evaluation. Adaptations of theoretical models to current-state interventions and integration of multiple, established models are needed to sustain prevention efforts and efficacy over time.